O discurso argumentativo na publicidade : uma análise verbo-visual - Barreto Neta, Elisa de Araújo (2010)
Publicity presents an efficient discourse which stimulates in people the consuming behavior, of either products or social causes. In order to have this happening, it uses verbal or non-verbal texts, arranged in commercials full of expressions of persuasion, in which one will find the ―ethos‖, the ―logos‖, and the ―pathos‖, wishing to intellectually and emotionally seduce the consumer. Among the social causes, one will find fund raising campaigns for philanthropic hospitals, which need more and more to diversify their sources of income, specially supported by contemporary movements of solidarity. Accordingly, the objective of this work is to analyze the argumentative strategies present in texts and images of a publicitary fund raising campaign for a philanthropic institution in the city of Recife. The corpus is the campaign material entitled ―Christmas Cards‖, destined to raise funds for a centennial hospital in the city, composed of three papers commercials issued between November and December of 2007. The method is qualitative and exploratory, and takes bibliographical analyses of the verbal-imaging discourses in the commercials as its main technical instruments. The approach is based on the idea that there is an articulation between an enunciation, a concrete annunciate and an announcement, which includes the situationality, the intertextuality and the intentionality as argumentative strategy. This dissertation, thus, brings up a reflection on the direction that the third sector is giving up to social publicity, great allied as it is to generate visibility to the social causes and this way to widen the discussion spaces, mainly because it brings together with its discourses messages that waken up the citizens consciousness and sensibility